2020
DOI: 10.1039/d0ra01610a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of resorcinol-based porous resin carbon material and its application in aqueous symmetric supercapacitors

Abstract: Activated preparation of environmentally friendly and sustainable carbon materials and their successful application in supercapacitor devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Such an origin of this effect was confirmed by the similar micropore volumes for all tested materials (values within the range of 0.18–0.23 cm 3 ·g −1 ), which clearly confirmed the presence of larger interparticle voids. The determined textural parameters were similar to the results reported by other researchers for resol-based carbon materials, which typically have BET surface areas within the range of 450–750 m 2 ·g −1 , regardless of morphology [ 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 84%
“…Such an origin of this effect was confirmed by the similar micropore volumes for all tested materials (values within the range of 0.18–0.23 cm 3 ·g −1 ), which clearly confirmed the presence of larger interparticle voids. The determined textural parameters were similar to the results reported by other researchers for resol-based carbon materials, which typically have BET surface areas within the range of 450–750 m 2 ·g −1 , regardless of morphology [ 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 84%
“…The absence of pores in the mesopore sizes from 2 to 4 nm in this electrode may be the reason for the inaccessibility of the pores at high current density. The specific capacitance obtained in this study is much higher compared to the values reported in literature for RF derived carbon-gels (aerogels/cryogels/xerogels) synthesised with a solvent exchange step prior to drying for retaining pores [ 17 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], and comparable to the recent studies [ 46 , 47 , 48 , 49 ] using KOH electrolyte.…”
Section: Resultssupporting
confidence: 83%
“…But the size of the curve increased slightly as the R/W ratio decreased with the largest one at R/W = 45, as expected from the highest SSA at R/W = 45 (Table S6 † ). A small hump observed on the CV curves can be attributed to the pseudo-faradaic reaction arising from the oxygen functional moieties on the electrode surface, 43 as supported by the XPS analysis ( Fig. 2c ).…”
Section: Resultsmentioning
confidence: 55%
“…However, most studies in the literature reported a maximum SSA athighertemperaturessuchas700, 43 800 44,45 or 900 °C. 46,47 The discrepancy of our data may be explained by the 2-step process (pyrolysis and then activation) employed in this study as opposed to the 1-step process (simultaneous pyrolysis and activation) used in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation